A Case Report of Ropeginterferon Alfa-2b for Polycythemia Vera during Pregnancy - Su-Yeon Bang; Sung-Eun Lee (Hematology Reports, 2023)
Myeloproliferative neoplasms (MPN) such as essential thrombocythemia (ET) and polycythemia vera (PV) are rare during pregnancy. However, they are harmful because they are associated with an increased risk of thromboembolic, hemorrhagic, or microcirculatory disturbances or placental dysfunction leading to fetal growth restriction or loss. Low-dose aspirin and low-molecular-weight heparin (LMWH) are recommended to reduce pregnancy complications, and interferon (IFN) is the only treatment option for cytoreductive therapy based on the likelihood of live birth in pregnant women with MPN. Since ropeginterferon alfa-2b is the only available IFN in South Korea, we present a case report of ropeginterferon alfa-2b use during pregnancy in an MPN patient. A 40-year-old woman who had been diagnosed with low-risk PV in 2017 and had been maintained on phlebotomy, hydroxyurea (HU), and anagrelide (ANA) for 4 years was confirmed as 5 weeks pregnant on 9 December 2021. After stopping treatment with HU and ANA, the patient showed a rapid increase in platelet count (1113 × 109/L to 2074 × 109/L, normal range, 150–450 × 109/L) and white blood cell count (21.93 × 109/L to 35.55 × 109/L, normal range, 4.0–10.0 × 109/L). Considering the high risk of complications, aggressive cytoreductive treatment was required, for which we chose ropeginterferon alfa-2b, as it is the only available IFN agent in South Korea. The patient underwent 8 cycles of ropeginterferon alfa-2b over 6 months during pregnancy and delivered without any neonatal or maternal complications. This case report highlights the importance of considering treatment options for MPN patients who are pregnant or planning a pregnancy, as well as the need for further investigation into the safety and efficacy of ropeginterferon alfa-2b in this population.